LOW DENSITY LIPOPROTEIN (LDL) CHOLESTROL: THE BAD CHOLESTROL - Mohapatra, Animesh K.; Jha, Shail Kumari (SCHOOL SCIENCE, 2011)
This article introduces cholesterol, its transport as a component of liproprotein and types of lipoproteins. Mechanism of plaque formation in arteries is also explained. High Density Lipoprotein (HDL) and Low Density Lipoprotein (LDL) cholesterol, their relative importance and foods that fight bad LDL cholesterol are discussed.